Double-seedlings and embryo-free seeds generated by genetic engineering - Xia, Yumei; Wang, Yao; Hu, Yuanyi; Zhan, Yijie; Dan, Junhao; Tang, Ning; Tian, Junyou; Cao, Mengliang (Frontiers in Plant Science, 2022)
Hybrid F1 plants can have increased yields due to the effects of heterosis, which is not maintained because of genetic segregation in the F2 generation. Apomixis can fix heterozygous genotypes, and is an ideal way to maintain heterosis in hybrid F1 seeds. Here, we designed an adventitious embryony production strategy that uses an embryogenesis gene, AtWUS, controlled by the ovule-specific promoter and a ribonuclease gene Barnase driven by the egg cell-specific promoter pDD45 in one T-DNA, which was co-transformed with a second T-DNA carrying a Barstar gene to inhibit the background expression of Barnase. We show that in rice (Oryza sativa), some seeds could grow two buds and roots independently, one of buds is diploid and the other is haploid, which is called double-seedlings. AtWUS plays a key role in the occurrence of embryogenesis without fertilization. Thus, we guess other cells of the embryo sac can developed into a haploid embryo except the egg cell by expression of AtWUS gene, and they share the endosperm with the diploid embryo resulting from fertilization of egg cell and sperm cell. We also demonstrated that single fertilization of the polar nuclei forms normal endosperm in embryo-free seeds due to the expression of the Barnase gene in the egg cell. The results are not what were expected based on the design of the experiments. In spite of this, the results obtained are informative and strongly suggest that endosperm development is an autonomously organized process in rice, independent of egg cell fertilization and embryo-endosperm communication. This provides novel insights into the induction of haploid embryos and lends theoretical support to successful clonal propagation using synthetic apomixis.